2001
DOI: 10.2105/ajph.91.4.564
|View full text |Cite
|
Sign up to set email alerts
|

Household solvent exposures and childhood acute lymphoblastic leukemia

Abstract: A B S T R A C TObjectives. This study explored the risk of childhood acute lymphoblastic leukemia (ALL) associated with participation by household members in hobbies or other home projects involving organic solvents.Methods. Participants in this casecontrol study were 640 subjects with ALL and 640 matched controls.Results. Childhood ALL was associated with frequent (>4 times/month) exposure to model building (odds ratio [OR] = 1.9; 95% confidence interval [95% CI] = 0.7, 5.8) and artwork using solvents (OR = 4… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
30
1
1

Year Published

2004
2004
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 62 publications
(33 citation statements)
references
References 22 publications
1
30
1
1
Order By: Relevance
“…Two SNPs (rs6214 and rs6218) were identified to be associated with childhood ALL risk. The epidemiologic data showed that more subjects in the case group than those in the control group had parental drinking history and house painting exposure during pregnancy or after birth, which is consistent with previous findings [46,47] indicating that parental alcohol consumption and decoration materials exposure are properly risk factors for childhood ALL. Further analysis between IGF1 3'UTR polymorphisms and parental drinking or house painting history confirmed the gene-environment interaction.…”
Section: Discussionsupporting
confidence: 90%
“…Two SNPs (rs6214 and rs6218) were identified to be associated with childhood ALL risk. The epidemiologic data showed that more subjects in the case group than those in the control group had parental drinking history and house painting exposure during pregnancy or after birth, which is consistent with previous findings [46,47] indicating that parental alcohol consumption and decoration materials exposure are properly risk factors for childhood ALL. Further analysis between IGF1 3'UTR polymorphisms and parental drinking or house painting history confirmed the gene-environment interaction.…”
Section: Discussionsupporting
confidence: 90%
“…Studies have examined the relationship between childhood leukemia and direct exposure to these chemicals (e.g., use of pesticides in the home) (Freedman et al 2001; Lowengart 1987) as well as secondary exposure, such as to parents’ clothing worn in an occupational setting where hydrocarbons are used and brought into the home to be laundered (Buckley et al 1989; Lowengart 1987; Shu et al 1999b). …”
Section: Environmental Factorsmentioning
confidence: 99%
“…Freedman et al (2001) conducted a case-control study of 640 subjects to examine the relationship between parental hobbies and home projects and incidence of childhood leukemia. ALL had a statistically significant association with prenatal exposure to painted homes (> 4 rooms) (OR = 1.7; 95% CI, 1.1–2.7) and to artwork with solvents (OR = 4.1; 95% CI, 1.1–15.1).…”
Section: Environmental Factorsmentioning
confidence: 99%
“…A study reported results on home exposure to solvents and childhood ALL (Freedman et al 2001). Only artwork at a frequency of more than four times a month was associated with an increased risk of ALL.…”
Section: Discussionmentioning
confidence: 99%